2019
DOI: 10.1055/a-1031-7328
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Casuarinin from Melaleuca leucadendra against Ethanol-Induced Gastric Ulcer in Rats

Abstract: Gastric ulcer is a major health problem. Current treatment options of gastric ulcer, including antagonists of histamine H2 receptor and inhibitors of the proton pump, do not cure gastric ulcers, but only provide temporary relief of symptoms and can be associated with severe side effects. The lack of effective and safe medications for this global health problem urges for the discovery of novel classes of compounds with potent activity and an acceptable safety profile. Ethanol-induced ulceration in rats was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…In contrast to COX‐1, COX‐2 is rarely expressed in normal tissues. However, after noxious stimulation, inflammatory cytokines, such as TNF‐α and IL‐6 are released, which in turn increases the expression of COX‐2 [40,41] . An increase in COX‐2 expression can aggravate gastric mucosal injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to COX‐1, COX‐2 is rarely expressed in normal tissues. However, after noxious stimulation, inflammatory cytokines, such as TNF‐α and IL‐6 are released, which in turn increases the expression of COX‐2 [40,41] . An increase in COX‐2 expression can aggravate gastric mucosal injury.…”
Section: Resultsmentioning
confidence: 99%
“…However, after noxious stimulation, inflammatory cytokines, such as TNF-α and IL-6 are released, which in turn increases the expression of COX-2. [40,41] An increase in COX-2 expression can aggravate gastric mucosal injury. The results of this study demonstrated that HP effectively inhibited the inflammatory cascade through the NF-кB/COX-2 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampal neurons were outlined, then the pathological changes in the different hippocampal regions were examined at high power (×400 magnification) in each group. The Lesion scoring system for pathological changes in different hippocampal regions was performed (Al-Sayed et al, 2020). Each animal was given a Lesion score between 0 and 3, for each of the three parameters, viz., neuronal damage, perineuronal edema, and glial cells infiltrates, where, 0 indicates no change, 1 indicates mild change (less than 15% of the examined samples), 2 indicates moderate change (16-35% of examined samples), and 3 indicates severe change (more than 35% of examined samples).…”
Section: Histopathological Analysismentioning
confidence: 99%
“…Group A: intragastric intubation using the quartz derivation without irradiation for seven constructive days Group B: no interventions Group C: OMEP (20 mg/kg) for seven constructive days [18] Group D: intragastric UVC irradiation for 24 s × 2 yields on day 1 and intubation without irradiation on day 2 to day 7 Group E: intragastric UVC irradiation for 48 s × 2 yields on day 1 and intubation without irradiation on day 2 to day 7…”
Section: Interventionsmentioning
confidence: 99%